ANALISIS PSIKOPAT TERHADAP MICHAEL MYERS DALAM FILM HALLOWEEN PRODUKSI DAVID GREEN - Tumampas, Riedel Yosua Verily; Sigarlaki, Stephani J.; Manus, Jeane Angela (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
ABSTRACTThis research is entitled "a psychopathic analysis of Michael Myers in the Halloween film produced by David Green." The thing that is done to research this research is that the writer first watches the film and then understands the contents of the story after that the writer collects data analysis or discussion Internet and this research also uses Stanton's theory of psychopathic characteristics in Michael Myers and this study also aims to identify psychopathic characteristics and also analyzes the factors that cause the main character to become a psychopath. It can be caused by several factors, for example, such as environmental factors, movies and also the internet and from this psychopath disease it can harm us, such as the occurrence of criminal acts. It is hoped that this research can be useful for readers and further researchers so that this research can be used as a reference, especially in analyzing psychopathic characters through film objects.Keywords: Psychopathic analysis, characteristics, films